Alexander Technique vs. Targeted Exercise for Neck Pain—A Preliminary Comparison - Jordan J. Becker; Tara L. McIsaac; Shawn L. Copeland; Rajal G. Cohen (Applied Sciences, 2021)
Background: Alexander technique private lessons have been shown to reduce chronic neck pain and are thought to work by different mechanisms than exercise. Group classes may also be effective and would be cost-effective. Design: A two-group pre-test/post-test design. Participants were assigned to either a general Alexander technique class or an exercise class designed to target neck pain. Both groups met over 5 weeks for two 60 min sessions/week. Participants: A total of 16 participants with chronic neck pain (aged 50+/−16 years) completed this study. Interventions: The Alexander class used awareness-building methods to teach participants to reduce habitual tension during everyday activities. The exercise class was based on physical therapy standard of care to strengthen neck and back muscles thought to be important for posture. Measures: We assessed neck pain/disability, pain self-efficacy, activation of the sternocleidomastoid muscles during the cranio-cervical flexion test, and posture while participants played a video game. Results: Both groups reported decreased neck pain/disability after the interventions. Sternocleidomastoid activation decreased only in the Alexander group. Conclusion: In this small preliminary study, Alexander classes were at least as effective as exercise classes in reducing neck pain and seemed to work via a different mechanism. Larger, multi-site studies are justified.